The complete mitochondrial genome of spearnose grenadier, Coelorinchus multispinulosus, Katayama, 1942 (Gadiformes: Macrouridae) - Sapto Andriyono; Ah-Ran Kim; Md. Jobaidul Alam; Hyun Park; Hyun-Woo Kim (Mitochondrial DNA. Part B. Resources, 2019)
The complete mitochondrial genome of Coelorinchus multispinulosus was determined using the MiSeq platform. The mitogenome of C. multispinulosus (15,937 bp) contained 13 protein-coding genes, 22 tRNAs, two ribosomal RNAs (12S and 16S), and a control region (D-Loop). The G + C content of its mitogenome was 44.69%, which was lower than A + T contents (55.31%). Unusual start codon (GTG) was identified in three protein-coding genes including COX1, ND2, and ND3. Incomplete stop codons (TA–/T–) were shown in six genes including COX1, COX2, COX3, ND3, ND4, and ATP6. Based on the phylogenetic tree with the currently reported mitogenomes in the family Macrouridae, C. multispinulosus was most closely related to Coelorinchus kishinouyei with 85% nucleotide sequence identity.